EFFECT OF ETHANOL EXTRACT OF SNAKE FRUIT‟S PEEL EFFECT ON URIC ACID AND CRP - Pribadi, Fajar Wahyu; -, Setiawati; Ati, Viva Ratih Bening; Widiartini, Catharina; Panuntun, Hilmi Puguh (Universitas Muhammadiyah Semarang, 2017)
Unhealthy diet that consisted of high purine, derived from protein, had caused an increasing hyperuricemia-related disease in community. Anti-oxidant activity of snake fruit‟s peel had antihyperuricemia effect due to the flavonoid content. This study aimed to investigate the effect of ethanol extract of snake fruit‟s peel in reducing uric acid serum & C-Reactive Protein (CRP) level and to find outthe most effective dosage of the activity. The rats were grouped into 6 groups (negative control, positive control, Allopurinol, dosage I (105 mg/kgbw extract), dosage II (210 mg/kgbw) and dosage III (420 mg/kgbw). All, except negative control groups were fed by standard diet pellet mixed with 20 mg/day goat brain for 15 days. Serum uric acid and CRP level of all groups was measured on day 0,9 and 16. The result showed that the uric acid serum level of extract groups was lower than control groups and therewas CRP reduction in extract groups. The most effective dosage for reducing serum uric acid level was 420 mg/kgbw. Keyword : snake fruit‟s peel, uric acid serum, C-Reactive Protein (CRP)